2x+12+2x=9x+18+10

Simple and best practice solution for 2x+12+2x=9x+18+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+12+2x=9x+18+10 equation:


Simplifying
2x + 12 + 2x = 9x + 18 + 10

Reorder the terms:
12 + 2x + 2x = 9x + 18 + 10

Combine like terms: 2x + 2x = 4x
12 + 4x = 9x + 18 + 10

Reorder the terms:
12 + 4x = 18 + 10 + 9x

Combine like terms: 18 + 10 = 28
12 + 4x = 28 + 9x

Solving
12 + 4x = 28 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
12 + 4x + -9x = 28 + 9x + -9x

Combine like terms: 4x + -9x = -5x
12 + -5x = 28 + 9x + -9x

Combine like terms: 9x + -9x = 0
12 + -5x = 28 + 0
12 + -5x = 28

Add '-12' to each side of the equation.
12 + -12 + -5x = 28 + -12

Combine like terms: 12 + -12 = 0
0 + -5x = 28 + -12
-5x = 28 + -12

Combine like terms: 28 + -12 = 16
-5x = 16

Divide each side by '-5'.
x = -3.2

Simplifying
x = -3.2

See similar equations:

| 5x+.4=3x-.2 | | 4/3(6)^3 | | 4/396)^3 | | (-4m)+(10m)+20-30= | | -32/7x=3 | | 3(4+y)=y+6 | | 5=-7y+4(y-4) | | 13y+1.8=-5y+3.6 | | 6(3x+2)=200 | | 18x^2+5-[3(x^2-3)+7]= | | 5/6x12=x | | 4x+8x(-2)+10= | | 3(2x-5)=4x-6 | | x-2+x=12 | | 35x+10y=355 | | (2x+7)(x-2)=2x^2 | | 10g+12-2g=6 | | 2-8x=121x+20 | | 16t^2+72t+520=h | | 22-5x=30-9x | | (X-w)y= | | 7n^2-n+12=0 | | 2m-8=5-8 | | 95=186-w | | g(x)=x^2+46 | | 14y=42+8y | | 2y^2-13t+20=0 | | 249=44-x | | 15*x+3=2x*12 | | 6n-18=4(n+3) | | 8x-22=3(3x+11)-6z | | 6c-90=4c-50 |

Equations solver categories